How generational replacement undermined the electoral resilience of Fianna Fáil - van der Eijk, Cees; Elkink, Johan A. (Oxford University Press, 2017)
This chapter focuses on party switching. The civil-war cleavage that differentiated the two main Irish parties, Fianna Fáil and Fine Gael, has been gradually diminishing in importance in recent decades. This trend reached a crescendo in 2011, when the incumbent Fianna Fáil party saw a dramatic decline in voter support, with swathes of its core voters switching to the main opposition party, Fine Gael. This volatility must be seen from the perspective of a generational replacement. To understand the potential for electoral switching, as opposed to change after the fact, the chapter investigates the configuration of voters’ preferences expressed through propensity to vote questions in the INES. The general framework provides theoretical tools better to understand the scale of Fianna Fáil’s defeat, as unique commitment to that party had declined markedly from the position a generation previously and it was thus more vulnerable to punishment following the crisis.